Ultrathin ultra-low carbon steel and manufacturing method thereof

By optimizing the smelting, heating, rolling and cooling processes, the temperature unevenness of the hot coil of extremely thin specifications of ultra-low carbon steel is solved, the plastic strain ratio uniformity and deep-draining performance of the material are improved, and energy consumption is reduced. Oxidation burns, improving surface quality.

CN119287268APending Publication Date: 2025-01-10МААНЬШАНЬ АЙРОН ЭНД СТИЛ КО ЛТД
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411246504.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

When producing extremely thin and ultra-low carbon steel in the traditional hot continuous rolling process, the final rolling temperature in the length direction of the hot coil has problems such as low head and tail and high middle, which leads to mixed crystal defects, affecting the strength and uniformity of the material, especially The plastic strain ratio fluctuates greatly, affecting the stamping performance of the material.

Method used

Adopt reasonable smelting, continuous casting, heating, rolling, cooling and coiling processes, including converter smelting, RH refining, low-temperature heating, 2-frame rough rolling and 7-frame fine rolling, segment cooling and coiling processes, control The casting blank is discharge temperature, rolling temperature and cooling rate to ensure that the tail temperature in the length direction of the casting blank is higher than the head, the relationship between the thickness of the intermediate blank and the thickness of the hot coil, the cumulative pressure reduction rate and lubrication process of the finishing rolling stand to realize the hot coil head , medium and tail mechanical properties uniformity.

Benefits of technology

Improves the uniformity of plastic strain ratio of extremely thin ultra-low carbon steel, reduces the yield strength, tensile strength and hardness fluctuations of the hot roll head, middle and tail, improves the deep-drawing performance of the material, and reduces the heating furnace energy. Consumption and oxidation burning improve surface quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287268A_ABST
    Figure CN119287268A_ABST
Patent Text Reader

Abstract

The invention discloses ultra-thin ultra-low carbon steel and a manufacturing method thereof. The ultra-thin ultra-low carbon steel comprises the following chemical components in percentage by weight: less than or equal to 0.0020% of C, less than or equal to 0.030% of Si, 0.08-0.15% of Mn, 0.040-0.080% of Ti, 0.010-0.050% of Nb, less than or equal to 0.0005% of B, less than or equal to 0.0040% of N, 0.015-0.050% of Als, less than or equal to 0.020% of Cr, less than or equal to 0.020% of Cu and the balance of Fe and inevitable impurities. According to the ultra-thin ultra-low carbon steel produced through the method, the hot coil yield strength is 130-150 MPa, the tensile strength is 270-290 MPa, the yield ratio is 0.48-0.60, the hardness is 43-48 HRB, and the plastic strain ratio r is 1.20-1.40. Compared with a conventional process, the ultra-low carbon steel hot coil produced through the method has the advantages that the yield strength of the ultra-thin ultra-low carbon steel hot coil is 130-150 MPa; the average yield strength corresponding to the head position, the middle position and the tail position of a hot coil is reduced by 39.6%-41.46%, the average tensile strength is reduced by 9.51%-11.42%, the average hardness is reduced by 6.59%-6.35%, the average yield ratio is reduced by 32.78%-34.76%, the average r is increased by 36.86%-45.62%, and the deep drawability of the material is improved by reducing the material strength, especially increasing the r value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ultra-low carbon steel production, and in particular to an ultra-thin ultra-low carbon steel and a manufacturing method thereof. Background Art

[0002] In recent years, with the increasing demand for "hot-heat cooling" of plate and strip products, the demand for ultra-thin (≤2.0mm) ultra-low carbon steel has continued to increase. According to the production process, ultra-thin strip steel can be produced in the thin slab continuous casting and rolling process and the traditional hot rolling process. Considering factors such as the number of inclusions, surface quality, and strength, the traditional hot rolling process is still the mainstream production process. Due to the use of the speed-up rolling process, the threading speed is close to the upper limit of the equipment capacity, the rolling speed of the head of the hot coil is lower than that of the middle part, the temperature drop exists at the tail of the intermediate billet, and the cooling rate of the outer ring of the hot coil is fast. The traditional hot rolling process produces ultra-low carbon steel with extremely thin specifications. The final rolling temperature of the hot coil in the length direction often has the problem of "low at the head and tail, high in the middle". The final rolling temperature of the head or tail of the hot coil is 30-60℃ or even higher than that of the middle position, resulting in the temperature of the head or tail of the hot coil being lower than the temperature of the austenite zone and rolling in the two-phase zone, which is prone to mixed crystal defects, and then leads to high strength at the head and tail of the ultra-low carbon steel hot coil, low plastic strain ratio, low strength in the middle, high plastic strain ratio, and large fluctuations in the mechanical properties of the head, middle and tail of the hot coil, especially the large fluctuations in the plastic strain ratio, which directly affect the stamping performance of the material and affect the use of downstream users. Therefore, the traditional hot rolling process produces ultra-thin ultra-low carbon steel coils with large fluctuations in mechanical properties, especially the plastic strain ratio.

[0003] Patents that have been published on improving the uniformity of material coiling performance, such as the patent with publication number CN107824619A, disclose a method for improving the uniformity of strip performance, which mainly adopts a stepped cooling method in the width direction of the strip to reduce the cooling water flow on both sides of the strip and improve the temperature uniformity in the width direction of the strip, thereby improving the uniformity of performance in the width direction of the strip. This method is mainly used to improve the uniformity of performance in the width direction of the strip, and the uniformity of performance in the length direction of the strip is not involved; Patents with publication numbers CN107983784B and CN112246910A both adopt segmented head and tail The shielding method improves the uniformity of the performance of the steel plate in the length direction. This method is suitable for medium and thick plates, but not for ultra-thin hot-rolled strip (thickness ≤ 2.0 mm); the patent with publication number CN113106208A mainly improves the uniformity of the performance of galvanized dual-phase steel in the length direction by optimizing the continuous annealing process; the patents with publication numbers CN103031419B and CN113249557A mainly use the U-type cooling process to improve the uniformity of the performance of the strip in the length direction, but the U-type cooling process is not suitable for solving the problem of large fluctuations in material performance in the length direction of ultra-thin hot coils due to low final rolling temperature and mixed crystal structure. The patents with publication numbers CN112063815A and CN110614280A mainly improve the temperature uniformity and performance uniformity of the strip in the length and width direction by adding online heat preservation cover equipment after the coiler. This method requires additional equipment investment and has no obvious effect on improving the performance uniformity of ultra-low carbon steel using high-temperature coiling technology.

[0004] In summary, the patents that have been applied for improving the uniformity of mechanical properties of steel strips have the following characteristics: (1) The research is for medium and thick plates; (2) The uniformity of the performance of steel strips in the longitudinal direction is improved by optimizing the continuous annealing process; (3) The improvement of the uniformity of the performance is concentrated in the width direction of the steel strip, and the length direction is not involved; (4) The uniformity of the performance of steel strips in the longitudinal direction is improved by segmented head and tail shielding or U-shaped cooling process; (5) By adding online heat preservation hood equipment. At present, there are many patent technologies that attempt to improve the uniformity of the mechanical properties of steel strips, but these methods mainly focus on improving the uniformity of the performance in the width direction of the steel strip, and the effect of improving the uniformity of the performance in the length direction is limited. In addition, some patent technologies improve the temperature uniformity of steel strips by adding online heat preservation hood equipment, but this requires additional equipment investment, and the effect of improving the uniformity of the performance of ultra-low carbon steel using high-temperature coiling process is not obvious. The above methods are not suitable for improving the uniformity of the mechanical properties of ultra-low carbon steel coils of extremely thin specifications, especially the uniformity of plastic strain ratio. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to propose an ultra-thin ultra-low carbon steel and a method for manufacturing the same. The present invention can solve the problem of large fluctuations in the tensile properties of ultra-thin ultra-low carbon steel produced by the traditional hot rolling process, especially the plastic strain ratio, through reasonable smelting, continuous casting, heating, rolling, cooling and coiling processes, and improve the uniformity of the mechanical properties of the ultra-low carbon steel, especially the plastic strain ratio.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] The invention provides an ultra-thin low-carbon steel. The chemical composition of the ultra-thin low-carbon steel is calculated by weight percentage as follows: C: ≤0.0020%, Si: ≤0.030%, Mn: 0.08-0.15%, Ti: 0.040-0.080%, Nb: 0.010-0.050%, B: ≤0.0005%, N: ≤0.0040%, Als: 0.015-0.050%, Cr≤0.020%, Cu≤0.020%, and the rest is Fe and unavoidable impurities.

[0008] As a further optimization scheme of the present invention, the hot-rolled ultra-thin low-carbon steel has a yield strength of 130-150 MPa, a tensile strength of 270-290 MPa, a yield strength ratio of 0.48-0.60, a hardness of 43-48 HRB, and a plastic strain ratio r=1.20-1.40; and the yield strength fluctuation range corresponding to the head, middle and tail of the hot-rolled coil is ≤20 MPa, the tensile strength fluctuation range is ≤20 MPa, and the plastic strain ratio r fluctuation range is ≤0.05.

[0009] The present invention also provides a method for preparing ultra-thin low-carbon steel, which comprises converter smelting, RH refining, continuous casting, heating, rolling, cooling and coiling processes.

[0010] As a further optimization scheme of the present invention, in the heating process, the furnace exit temperature of the ingot is 1100-1150°C, and the tail temperature of the ingot in the length direction is 20-40°C higher than the head temperature, and the ingot is in the furnace for 150-200 minutes.

[0011] As a further optimization scheme of the present invention, in the rolling process, a 2-stand rough rolling and a 7-stand finishing hot rolling mill group is used for rolling.

[0012] As a further optimization scheme of the present invention, rough rolling adopts 3+5 rolling mode (R1 and R2 rough rolling mills have 3 and 5 rolling passes respectively), high-pressure descaling water is turned on for each rolling pass of rough rolling, the insulation cover between the rough rolling and finishing rolling mills is turned on, the rough rolling final rolling temperature R2DT=950~1000℃, and the finishing rolling inlet temperature FET=870~920℃.

[0013] As a further optimization scheme of the present invention, the intermediate billet thickness H and the hot coil finished product thickness h need to satisfy the relationship: H = (20-25)h.

[0014] As a further optimization scheme of the present invention, the cumulative reduction rates of the finishing rolling stands F1-F2 and F3-F7 are ≤70% and ≥85% respectively; both rough rolling and finishing rolling adopt a constant speed rolling mode, the rolling speed is ≥12m / s, and the final rolling temperature FDT=820~870℃.

[0015] As a further optimization scheme of the present invention, the finishing rolling F2-F6 stands adopt a roll gap lubrication process, the concentration of the oil-water mixture is 0.30%-0.60%, and the flow rate of the roll gap lubricating liquid is 80-120 ml / min.

[0016] As a further optimization scheme of the present invention, in the cooling and coiling process, a segmented cooling mode is adopted, the cooling rate of the first stage is 5-10°C / s, the cooling rate of the second stage is 20-40°C / s, and the coiling is carried out after cooling. The coiling temperature CT is 670-720°C, and the hot coil is air-cooled to room temperature after coiling.

[0017] The characteristics of chemical composition and production process are as follows:

[0018] In the chemical composition design of the present invention, the content of C, Si, Mn, Als, and Ti elements is the same as that of the existing process, but the content of residual alloy elements Cu and Cr is limited. Cu≤0.020% is mainly to avoid Cu segregation at the grain boundary during heating, which is not conducive to the stamping performance of the material. Cr≤0.020% is mainly based on the fact that under the low-temperature heating conditions of the present invention, Cr will increase the adhesion between the oxide scale and the matrix, which is not conducive to the removal of the surface oxide scale, and thus is not conducive to the stamping performance of the material; at the same time, Cu and Cr, as solid solution strengthening elements, will both improve the strength of the material; B:≤0.0005%, B element, as a typical grain boundary segregation element, will significantly inhibit the nucleation and growth of proeutectoid ferrite recrystallization, refine the grain size of the material, improve the material strength, and at the same time, it will also reduce the {111} texture (this texture is conducive to improving the deep drawing performance of the material.) component content, reduce the material plastic strain ratio, and is not conducive to the deep drawing performance of the material.

[0019] In the heating process design of the present invention, the temperature of the billet out of the furnace is 1100-1150°C, which is mainly based on the need to ensure the entrance temperature of the finishing rolling, and the use of a low-temperature heating process is beneficial to reducing oxidation and burning, the thickness of the oxide scale, and is beneficial to improving the surface quality of the material and the hot rolling yield rate. The tail temperature of the billet in the length direction is 20-40°C higher than the head temperature, which is mainly based on the constant speed rolling of the finishing mill, which is beneficial to improving the uniformity of the hot coil through-coiling performance.

[0020] In the rolling process design of the present invention, the high-pressure water descaling is turned on in each rough rolling pass and the insulation cover between the rough rolling and finishing rolling units is turned on to ensure that the finishing rolling inlet temperature FET is 870-920°C. Too high FET causes the finishing rolling F1-F5 frames to be in the austenite phase or two-phase temperature zone. On the one hand, rolling in the two-phase zone is prone to rolling instability, mixed crystals, and deterioration of material performance uniformity; on the other hand, the cumulative rolling reduction of the material in the ferrite zone cannot be guaranteed, and the ferrite grains cannot be fully recrystallized and grown, resulting in no obvious coarsening of the ferrite grains, which is not conducive to reducing the strength of the material. The intermediate billet thickness H and the hot coil finished product thickness h must satisfy the relationship: H = (20-25) h. Properly increasing the intermediate billet thickness is conducive to reducing the intermediate billet temperature drop and increasing the intermediate billet temperature. If the intermediate billet thickness is too thin, it is easy to cause excessive temperature drop at the head and tail of the intermediate billet, and a larger temperature difference between the head and tail of the hot coil, which is not conducive to improving the uniformity of the hot coil through-rolling performance; if the intermediate billet thickness is too thick, the rolling pressure of the finishing mill is too large, which is not conducive to the plate shape control of the hot rolled product. The finishing rolling F1-F2 stand is in the transition temperature area between the low temperature area of ​​the two-phase zone and the high temperature area of ​​the ferrite phase. Based on the consideration of rolling stability, the cumulative reduction rate of the F1-F2 stand is ≤70%, while the F3-F7 stand is in the medium and high temperature area of ​​the ferrite phase transformation. In order to promote the dynamic recrystallization of ferrite, control the uniformity of the ferrite grain size and the coarsening effect of the ferrite grains, it is necessary to ensure that the cumulative reduction rate in the ferrite phase transformation area is ≥85%. The main purpose of using lubrication rolling process in F2~F6 finishing mills is to reduce the friction coefficient between the roller and the surface of the rolled piece, reduce the shear strain caused by friction and the unfavorable {110} texture caused by uneven deformation, control the consistency of the texture in the thickness direction of the rolled piece, and is conducive to the formation of {111} texture to improve the deep drawing performance of the material. FDT = 820~870℃, the purpose is that this temperature range is in the ferrite phase transformation region, the deformation resistance of the rolled piece is not increased compared with the rolling in the austenite region, which is conducive to improving the stability of the rolling process and the plate shape. When FDT < 820℃, the deformation resistance of the rolled piece is significantly increased, resulting in a significant increase in rolling pressure, which is not conducive to rolling stability. Constant speed rolling and rolling speed ≥ 12m / s are adopted, mainly based on reducing the residence time of the rolled piece in F1 and F2 stands, improving rolling stability, and controlling the uniformity of the final rolling temperature and coiling temperature of the hot coil, which is conducive to improving the uniformity of the hot coil performance.

[0021] The present invention adopts a segmented cooling mode in the cooling process design, firstly performs slow cooling at 5-10°C / s, and the slow cooling after rolling can reduce the supercooling and the ferrite nucleation rate. At the same time, the high coiling temperature of 670-720°C is matched, so that the ferrite can be recovered or completely statically recrystallized, and the ferrite grains can grow quickly and fully, which is beneficial to the reduction of material strength and the improvement of plastic strain ratio.

[0022] The beneficial effects achieved by the present invention are as follows:

[0023] The ultra-thin ultra-low carbon steel produced by the present invention has a hot coil yield strength of 130-150 MPa, a tensile strength of 270-290 MPa, a yield strength ratio of 0.48-0.60, a hardness of 43-48 HRB, and a plastic strain ratio r of 1.20-1.40. Compared with conventional processes, the ultra-low carbon steel hot coil produced by the present invention has an average yield strength corresponding to the head, middle and tail positions of the hot coil reduced by 39.6-41.46%, an average tensile strength reduced by 9.51-11.42%, an average hardness reduced by 6.59-6.35%, an average yield strength ratio reduced by 32.78-34.76%, and an average r increased by 36.86-45.62%. The reduced material strength, especially the increased r value, is beneficial to improving the deep drawing performance of the material.

[0024] Compared with conventional processes, the present invention solves the problem of mixed crystal structure at the head and tail of ultra-thin ultra-low carbon steel hot coils. The yield strength fluctuation range corresponding to the head, middle and tail of the hot coil is ≤20MPa, the tensile strength fluctuation range is ≤20MPa, the hardness fluctuation range is ≤5HRB, and the plastic strain ratio r fluctuation range is ≤0.05. The uniformity of the hot coil's through-coiling strength, hardness and plastic strain ratio is significantly improved.

[0025] The present invention adopts low-temperature heating and low-temperature rolling processes. On the one hand, it can effectively reduce the gas consumption of the heating furnace by 0.15 GJ / t material, which is equivalent to reducing the energy consumption cost of the heating furnace by about 5 yuan / t material; on the other hand, it can effectively reduce the oxidation and burning of the ingot and increase the hot rolling yield by about 0.15%; furthermore, low-temperature heating and low-temperature rolling are beneficial to improving the surface quality of the strip steel products. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is the deformation resistance-deformation temperature curve of the ultra-low carbon steel under different strain amounts in Example 1 of the present invention.

[0027] Figure 2 This is a microstructure picture of the ultra-low carbon steel of Example 1 of the present invention (without mixed crystal problem).

[0028] Figure 3 This is a microstructure picture of the ultra-low carbon steel of comparative example 1 (there is a mixed crystal problem). DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific embodiments, but it should not be understood as limiting the present invention and is only used as an example.

[0030] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.

[0031] The chemical composition weight percentage of the ultra-thin low-carbon steel provided by the present invention is: C≤0.0020%; Si:≤0.030%; Mn:0.08-0.15%; Ti:0.040-0.080%; Nb:0.010-0.050%; B:≤0.0005%; N:≤0.0040%; Als:0.015-0.050%; Cr≤0.020%; Cu≤0.020%; the rest is Fe and inevitable inclusions. Converter smelting, RH refining, continuous casting, heating, rolling, cooling and coiling processes are carried out.

[0032] The chemical compositions of the embodiments and comparative examples are shown in Table 1, the hot rolling temperature parameters of the embodiments and comparative examples are shown in Table 2, the lubrication and cooling processes of the embodiments and comparative examples are shown in Table 3, the mechanical properties and fluctuation amplitudes of the embodiments and comparative examples are shown in Table 4, and the average mechanical properties of the hot coil heads, middle and tails of the embodiments and comparative examples are shown in Table 5.

[0033] Table 1 Chemical composition of the embodiments and comparative examples (mass percentage, wt%)

[0034] serial number C Si Mn Ti Nb B N Als Cr Cu Example 1 0.0011 0.004 0.10 0.061 0.015 0.0002 0.0025 0.019 0.010 0.007 Example 2 0.0015 0.002 0.11 0.055 0.025 0.0003 0.0021 0.031 0.008 0.006 Example 3 0.0013 0.003 0.15 0.071 0.037 0.0004 0.0031 0.042 0.007 0.008 Comparative Example 1 0.0014 0.002 0.11 0.055 0.025 0.0010 0.0021 0.031 0.008 0.006 Comparative Example 2 0.0011 0.004 0.10 0.061 0.015 0.0002 0.0025 0.019 0.010 0.007 Comparative Example 3 0.0010 0.001 0.12 0.050 0.020 0.0004 0.0018 0.033 0.012 0.008 Comparative Example 4 0.0013 0.002 0.11 0.065 0.032 0.0003 0.0030 0.035 0.010 0.007 Comparative Example 5 0.0012 0.001 0.12 0.050 0.020 0.0004 0.0018 0.033 0.012 0.008 Comparative Example 6 0.0010 0.001 0.12 0.050 0.020 0.0004 0.0018 0.033 0.012 0.008

[0035] Table 2 Hot rolling temperature parameters of the embodiments and comparative examples

[0036]

[0037]

[0038] Table 3 Lubrication and cooling process parameters of the embodiments and comparative examples

[0039]

[0040] Table 4 Mechanical properties and fluctuation range of examples and comparative examples

[0041]

[0042] Table 5 Average mechanical properties of the head, middle and tail of the hot coil in the embodiments and comparative examples

[0043]

[0044]

[0045] The above test results show that the hot-rolled ultra-thin ultra-low carbon steel manufactured by the present invention has a yield strength of 130-150 MPa, a tensile strength of 270-290 MPa, a yield strength ratio of 0.48-0.60, a hardness of 43-48 HRB, and a plastic strain ratio r=1.20-1.40; and the yield strength fluctuation range corresponding to the head, middle and tail of the hot-rolled coil is ≤20 MPa, the tensile strength fluctuation range is ≤20 MPa, and the plastic strain ratio r fluctuation range is ≤0.05, and the uniformity of the hot-rolled strength, hardness and plastic strain ratio is significantly improved.

[0046] According to Comparative Examples 1 to 6, it can be obtained that only when the chemical composition and production process of the steel are controlled according to the present invention, can the technical effect of the present invention be obtained. Otherwise, if only the chemical composition of the steel meets the requirements of the present invention but the key process parameters of the production process are not controlled outside the scope of the present invention, it will lead to higher mechanical properties, lower plastic strain ratio and larger fluctuation amplitude.

[0047] Figure 1 The deformation resistance-deformation temperature curve of the test steel of the present invention under different strain values ​​is shown in FIG. Figure 1 It can be seen that the deformation resistance of the material corresponding to the deformation temperature range of 820-870℃ is equivalent to that corresponding to 900-930℃, which provides a reference for the test steel to adopt low final rolling temperature process. Figure 2 This is a microstructure picture of the ultra-low carbon steel of Example 1 of the present invention. Figure 2 It can be seen that the ultra-low carbon steel structure manufactured by the present invention has no mixed crystal problem. Figure 3 This is a picture of the organization of the ultra-low carbon steel of Example 1. Figure 3 It can be seen that the structure of the ultra-low carbon steel produced in Comparative Example 1 has a mixed crystal problem. This shows that the present invention solves the problem of mixed crystals in the head and tail positions of ultra-thin ultra-low carbon steel hot coils.

[0048] The above description only provides a specific exemplary description of the present invention. It should be noted that the specific implementation of the present invention is not limited to the above method. As long as various non-substantial improvements are made using the technical concept and technical solution of the present invention, or the technical concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. An ultra-thin low-carbon steel, characterized in that: The chemical composition of the ultra-thin low-carbon steel is calculated by weight percentage as follows: C: ≤0.0020%, Si: ≤0.030%, Mn: 0.08-0.15%, Ti: 0.040-0.080%, Nb: 0.010-0.050%, B: ≤0.0005%, N: ≤0.0040%, Als: 0.015-0.050%, Cr≤0.020%, Cu≤0.020%, and the rest is Fe and unavoidable impurities.

2. The ultra-thin low-carbon steel according to claim 1, characterized in that: The hot-rolled ultra-thin low-carbon steel has a yield strength of 130-150MPa, a tensile strength of 270-290MPa, a yield strength ratio of 0.48-0.60, a hardness of 43-48HRB, and a plastic strain ratio r=1.20-1.40; and the yield strength fluctuation range corresponding to the head, middle and tail of the hot-rolled coil is ≤20MPa, the tensile strength fluctuation range is ≤20MPa, and the plastic strain ratio r fluctuation range is ≤0.

05.

3. A method for preparing the ultra-thin low-carbon steel as claimed in claim 1 or 2, characterized in that: The preparation method comprises converter smelting, RH refining, continuous casting, heating, rolling, cooling and coiling processes.

4. The method for preparing ultra-thin low-carbon steel according to claim 3, characterized in that: In the heating process, the temperature of the ingot out of the furnace is 1100-1150°C, and the temperature of the tail of the ingot in the length direction is 20-40°C higher than the temperature of the head. The ingot is kept in the furnace for 150-200 minutes.

5. The method for preparing ultra-thin low-carbon steel according to claim 3, characterized in that: In the rolling process, a 2-stand rough rolling and a 7-stand finishing hot rolling mill are used for rolling.

6. The method for preparing ultra-thin low-carbon steel according to claim 5, characterized in that: The rough rolling adopts the 3+5 rolling mode. The high-pressure descaling water is turned on for each rolling pass of the rough rolling, the insulation cover between the rough rolling and finishing rolling units is turned on, the rough rolling final rolling temperature R2DT=950~1000℃, and the finishing rolling inlet temperature FET=870~920℃.

7. The method for preparing ultra-thin low-carbon steel according to claim 5, characterized in that: The intermediate billet thickness H and the hot coil finished product thickness h must satisfy the relationship: H = (20-25)h.

8. The method for preparing ultra-thin low-carbon steel according to claim 5, characterized in that: The cumulative reduction rates of the finishing rolling stands F1-F2 and F3-F7 are ≤70% and ≥85% respectively; both rough rolling and finishing rolling adopt a constant speed rolling mode, with a rolling speed ≥12m / s and a final rolling temperature FDT=820-870°C.

9. The method for preparing ultra-thin low-carbon steel according to claim 5, characterized in that: The finishing rolling F2~F6 stands use the roll gap lubrication process, the oil-water mixture concentration is 0.30%~0.60%, and the roll gap lubricating liquid flow rate is 80~120ml / min.

10. The method for preparing ultra-thin low-carbon steel according to claim 3, characterized in that: In the cooling and coiling process, a segmented cooling mode is adopted. The cooling rate of the first stage is 5-10°C / s, and the cooling rate of the second stage is 20-40°C / s. After cooling, coiling is carried out. The coiling temperature CT is 670-720°C. After the hot coil is coiled, it is air-cooled to room temperature.

Citation Information

Patent Citations

  • Method for improving performance uniformity of steel roll of Ti microalloyed high strength machinery

    CN103031419B

  • Method for improving performance uniformity of strip steel

    CN107824619A

  • A method for improving the uniformity of properties of hot-rolled steel sheets

    CN107983784B

  • Online hot roll temperature uniformizing treatment method

    CN110614280A

  • Method for improving performance uniformity of finished product through heat preservation and slow cooling after rolling

    CN112063815A